The Severity of Dependence Scale (SDS) for Codeine: Preliminary Investigation of the Psychometric Properties of the SDS in an Online Sample of Codeine Users From the UK - Deluca, Paolo; Foley, Michelle; Dunne, Jacklyn; Kimergård, Andreas (Frontiers in Psychiatry, 2021)
Objective: Investigate the psychometric properties of the Severity of Dependence Scale (SDS) for codeine and its association with aberrant codeine related behaviours. Design: A voluntary and uncompensated cross-sectional online survey. Setting: UK online population (≥18 years). Respondents: 286 respondents (66% women) who had used codeine containing medicines in the last 3 months. Results: Of the respondents (mean age = 35.4 years, SD = 12.5), more than half were employed. Only 3.5% respondents reported no income. The majority of respondents (45.1%) primarily obtained prescription-only codeine from a consultation with a health professional, whilst 40.9% mainly purchased ‘over-the-counter’ codeine containing medicines in a pharmacy without a medical prescription. Principal component analysis indicated a single factor solution accounting for 75% of the variance. Factor loadings ranged from 0.83 to 0.89. Cronbach’s Alpha was high (α = 0.92). Several behaviours relating to codeine use were found to significantly predict probable codeine dependence. These included: daily codeine use in the last 3 months (OR = 66.89, 95% CI = 15.8−283.18); tolerance to codeine (OR = 32.14, 95% CI = 13.82−74.75); problems with role responsibility due to intoxication (OR = 9.89, 95% CI = 4.95−19.78); having sought advice on the internet to manage codeine use (OR = 9.56, 95% CI = 4.5−20.31); history of alcohol or drug treatment (OR = 3.73, 95% CI = 1.88−7.43). Conclusions: The SDS was acceptable and feasible to use to assess probable psychological codeine dependence in an online sample of people using codeine containing medicines. SDS scores were associated with behaviours known to be indicators of codeine dependence. Studies are needed in well-defined populations of people who use codeine to test the different aspects of psychometry of the scale compared against ‘gold standard’ criterion (DSM diagnosis).